2014
DOI: 10.1038/npjpcrm.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of pre-bronchodilator FEV1/FEV6 from microspirometry to detect airflow obstruction in primary care: a randomised cross-sectional study

Abstract: Background:Forced expiratory volume in 1s/forced expiratory volume in 6 s ( FEV1/FEV6) assessment with a microspirometer may be useful in the diagnostic work up of subjects who are suspected of having COPD in primary care.Aim:To determine the diagnostic accuracy of a negative pre-bronchodilator (BD) microspirometry test relative to a full diagnostic spirometry test in subjects in whom general practitioners (GPs) suspect airflow obstruction.Methods:Cross-sectional study in which the order of microspirometry and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
(39 reference statements)
2
27
0
Order By: Relevance
“…The second study evaluated the NPV of handheld flow meters among a small sample (n=54) of ex-smokers aged ≥50 years who had been referred for diagnostic spirometry by their GP. 33 The NPV was estimated at 94.4% (95% CI 86.4% to 98.5%) when using the fixed ratio of FEV 1 /forced vital capacity (FVC) <0.7 to define airflow obstruction. Both findings are in keeping with our meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The second study evaluated the NPV of handheld flow meters among a small sample (n=54) of ex-smokers aged ≥50 years who had been referred for diagnostic spirometry by their GP. 33 The NPV was estimated at 94.4% (95% CI 86.4% to 98.5%) when using the fixed ratio of FEV 1 /forced vital capacity (FVC) <0.7 to define airflow obstruction. Both findings are in keeping with our meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend that three reproducible spirometry readings should be produced (van den Bemt et al, 2014), and must meet criteria from relevant guidelines (Levy et al, 2010;Sansores et al, 2013;Celli et al, 2015;Roberts et al, 2016;Kotaki et al, 2017), by well-trained staff (Spyratos et al, 2012). In addition, relevant literature states that 400 micrograms of albuterol or salbutamol is the recommended dose for postbronchodilator spirometry (Miller et al, 2005;Weiss et al, 2014;van den Bemt et al, 2014).…”
Section: Correctly Defining Airway Obstructionmentioning
confidence: 99%
“…Some studies state that for pre-bronchodilator microspirometry, a fixed cut-off point of FEV1/FEV6 <0.73 is now preferred over the previous FEV1/FVC <0.70 to indicate airflow obstruction in pre-bronchodilator microspirometry (van den Bemt et al, 2014). This was suggested due to patients with COPD being missed, as the cut-off point was too low (Thorn et al, 2012).…”
Section: Correctly Defining Airway Obstructionmentioning
confidence: 99%
“… 12 Several studies have concluded that hand-held screening devices including the COPD-6 and PiKo-6 device are reliable in screening for airway obstruction and selecting subjects for further diagnostic workup. 13 20 A recent meta-analysis concluded that the accuracy of FEV 1 /FEV 6 measured by hand-held devices seems to be lower than spirometry, but sufficiently accurate to screen for airway obstruction. 21 …”
Section: Introductionmentioning
confidence: 99%